The epidemiology and unmet need of migraine in five european countries: results from the national health and wellness survey - Gianluca Coppola; Joshua D. Brown; Amanda R. Mercadante; Sheila Drakeley; Nikoletta Sternbach; Aaron Jenkins; Karin Hygge Blakeman; Astrid Gendolla (BMC Public Health)
Abstract Background Despite the high global prevalence, burden, and direct and indicated costs, migraines are often under-diagnosed and undertreated. Understanding the prevalence of migraine and unmet needs is crucial for improving diagnosis and treatment across Europe (EU) countries; however, real-world studies are limited. Methods This retrospective cross-sectional survey utilized weighted patient-reported data from the 2020 National Health and Wellness Survey (NHWS) in five EU (5EU) countries (France, Germany, United Kingdom [UK], Italy, and Spain). The survey included adults aged ≥ 18 years who self-reported experiencing migraines in the past 12 months and had a physician’s diagnosis. The survey assessed migraine prevalence by age and sex. Other measures included migraine characteristics, disability assessment, migraine frequency (monthly migraine days [MMDs] and monthly headache days [MHDs], menstrually-related migraine, treatment patterns, and provider characteristics. Results The study included 7,311 respondents with diagnosed migraines, representing an estimated 30.5 million adults with a weighted prevalence of 11.5% in the 5EU. Spain had the highest prevalence (14.0%), followed by Italy, France, UK, and Germany. Migraine prevalence was highest in the age group of 30–39 years, and females had nearly twice the prevalence compared to males. About 56% of respondents reported disability due to migraines, with highest percentage reported in Germany (66.0%). About 46% of female respondents reported experiencing menstrually-related migraines. One-fourth of the study respondents reported > 4 MMDs and 56.2% reported > 4 MHD. Current treatment patterns revealed that 79.7% of respondents were receiving some form of migraine treatment, with non-steroidal anti-inflammatory drugs (NSAIDs), analgesics, and triptans being the most commonly reported prescription medications. Primary care physicians (PCPs) were the most common providers diagnosing migraines, followed by neurologists. Conclusions In the 5EU, one-fourth of diagnosed respondents reported > 4 MMDs, and 56.2% reported > 4 MHDs. Nearly half of females experienced menstrually-related migraines. Although most patients reported taking medication for migraine, severe disability and medication overuse were observed. PCPs were the main treatment providers, highlighting the need for improved expertise and referrals to specialists. Further research is required for a better understanding of the disparities between migraine frequency and treatment approaches.